Vibrio cholerae interactions with Mytilus galloprovincialis hemocytes mediated by serum components - Canesi, Laura; Pezzati, Elisabetta; Stauder, Monica; Grande, Chiara; Bavestrello, Margherita; Papetti, Adele; Vezzulli, Luigi; Pruzzo, Carla (Frontiers in Microbiology, 2013)
Edible bivalves (e.g., mussels, oysters) can accumulate large amount of bacteria in their tissues and act as passive carriers of pathogens to humans. Bacterial persistence inside bivalves depends, at least in part, on hemolymph anti-bacterial activity that is exerted by both serum soluble factors and phagocytic cells (i.e., the hemocytes). It was previously shown that Mytilus galloprovincialis hemolymph serum contains opsonins that mediate D-mannose-sensitive interactions between hemocytes and V. cholerae O1 El Tor bacteria that carry the Mannose–Sensitive Hemagglutinin (MSHA). These opsonins enhance phagocytosis and killing of vibrios by facilitating their binding to hemocytes. Since V. cholerae strains not carrying the MSHA ligand (O1 classical, non O1/O139) are present in coastal water and can be entrapped by mussels, we studied whether in mussel serum, in addition to opsonins directed towards MSHA, other components can mediate opsonization of these bacteria. By comparing interactions of O1 classical and non O1/O139 strains with hemocytes in ASW and serum, it was found that M. galloprovincialis serum contains components that increase by at approximately two fold their adhesion to, association with and killing by hemocytes. Experiments conducted with high and low molecular mass fractions obtained by serum ultrafiltration indicated that these compounds have molecular mass higher than 5000 Da. Serum exposure to high temperature (80°C) abolished its opsonizing capability suggesting that the involved serum active components are of protein nature. Further studies are needed to define the chemical properties and specificity of both the involved bacterial ligands and hemolymph opsonins. This information will be central not only to better understand V. cholerae ecology, but also to improve current bivalve depuration practices and properly protect human health.